The Ethics and Aesthetics of Architecture: The Anglican Reception of Roman Baroque Churches - Anne-Francoise Morel (Architectural Histories, 2016)
For Anglican travellers in Italy, Rome had an ambiguous status. It was the seat both of high culture and of ‘superstitious’ Roman Catholic practices, including art and architecture. These extremes culminated in church buildings. This article studies the perception and reaction of English travellers in Rome towards architecture of the Roman Catholic Church and its influence on English church architecture. It will reveal the church building as an aesthetic object, in addition to possessing religious qualities, through the analysis of printed travelogues and engravings that circulated amongst the English Grand Tour travellers. By analyzing the travelogue discourse — with particular attention to descriptions of specific church buildings and any intentional omissions in these descriptions — and examining the relationship between these discourses and contemporary English aesthetic theories, I will demonstrate how a certain appreciation for Roman Baroque church architecture was made acceptable and could even inspire the design of English church architecture. As will become clear, the process of travel included the separation of moral and artistic values in aesthetic appreciation. This separation made the cultural transfer between Italy and England possible in the 17th and early 18th centuries.